The Relationship of Service Quality, Pricing, and Digital Marketing with Customer Revisit Intention - Siti Hairiah; Sumijatun Sumijatun; Rr. Tutik Sri Hariyati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Patient revisit intention is an important indicator for evaluating hospital service performance, as it reflects patient satisfaction and loyalty. This study aims to analyze the effect of service quality, tariffs, and digital marketing on patient revisit intentions at Bhayangkara Kediri Hospital in 2025, both partially and simultaneously. This research employs a quantitative approach with an observational analytic design and a cross-sectional method. The study population included all outpatient patients who revisited the hospital from June to August 2024, totaling 18,317 patients, and a sample of 110 respondents was selected using purposive sampling based on inclusion criteria, calculated with Slovin’s formula and supported by a power test. Data were collected using structured questionnaires that had been tested for validity and reliability, and subsequently analyzed using multiple linear regression. The results indicate that, partially, service quality (X₁) has a positive and significant effect on patient revisit intention (β = 0.147; t = 3.297; p = 0.001), as do tariffs (X₂) (β = 0.173; t = 2.453; p = 0.016) and digital marketing (X₃) (β = 0.299; t = 4.158; p < 0.001). Simultaneously, all three independent variables significantly affect patient revisit intention (F = 38.336; p < 0.001), with a coefficient of determination (R²) of 0.520, indicating that 52% of the variation in revisit intention is explained by the study variables, while 48% is influenced by other factors. These findings emphasize that improving service quality and optimizing digital marketing are the main factors in strengthening patient loyalty, while tariffs act as a supporting variable in patients’ decision to revisit.